Advances in novel SDC@Al2O3 core−shell electrolyte for low‐temperature solid oxide fuel cell. Issue 6 (29th January 2022) - Xiang, Yuhao; Zheng, Dan; Zhou, Xiaomi; Cai, Hongdong; Wang, Kai; Xia, Chen; Wang, Xunying; Dong, Wenjing; Wang, Hao; Wang, Baoyuan
Abstract: The preparation of electrolyte with excellent ionic conduction is an important development direction in the practical application of solid oxide fuel cell (SOFC). Traditional methods to improve ion conduction was structure doping to develop electrolyte materials. In this work, the ionic conductor Ce0.8 Sm0.2 O2‐δ (SDC) was modified by insulator Al2 O3 to enhance ion conduction and apply as electrolytes for the SOFC. The transmission electron microscopy (TEM) characterization clearly clarified that a thin Al2 O3 layer in the amorphous state coated on SDC to form the SDC@Al2 O3 core−shell structure. The SDC@Al2 O3 electrolyte with the core−shell structure possesses a super ionic conductivity of 0.096 S cm −1 and results in advanced cell performance of 1190 mW cm −2 at 550°C. The X‐ray photoelectron spectroscopy (XPS) analysis revealed that the concentration of oxygen vacancies in the SDC@Al2 O3 core–shell structure significantly improved in comparison with pure SDC, the newly produced oxygen vacancies can promote the oxygen ion transport. Moreover, the interface between SDC and Al2 O3 provides a fast channel for the proton transport. In addition, the SDC‐based SOFC was usually suffered from the reduction of the SDC electrolyte and the accompanying generated electron conduction should deteriorate the cell performance, this is the main challenge for the SDC electrolyte application. In our case, the Al2 O3 shell on the SDC surface not only can avoid the contact between SDC and hydrogen to eliminate the reduction of SDC but also can restrain electron conduction due to the electron insulation characteristic of the Al2 O3 shell. This work demonstrates an efficient approach to develop the advanced low‐temperature SOFC technology from material fundamentals. Abstract : The ion conduction mechanism schematic diagram, and I–V and I–P characteristics for the SDC@Al2 O3 cells with different Al2 O3 contents.